Trisomy of 8q22.3 q23-qter following an unbalanced 1;8 translocation in a boy with multiple anomalies - Ergun, Mehmet Ali; Balcı, Sevim; Konaç, Ece; Kan, Derya; Menevşe, Sevda; Bartsch, Oliver (The Turkish Journal of Pediatrics, 2004)
An 11-month-old boy was first referred with global developmental delay, pallor and heart defects (ASD, VSD, mitral and tricuspid valve insufficiency). He also had facial abnormalities. Standard karyotyping showed additional material on one chromosome 1p homolog, and fluorescence in situ hybridization (FISH) indicated an unbalanced translocation of 1pter p36.33 and 8q22.3 q23. The breakpoint on p was found to reside very close to the telomere, making this a rare case of "almost pure" trisomy of 8q22.3 q23-qter, without a significant partial 1p36 monosomy by FISH technique. The patient’s face resembled the peculiar face in previously reported cases of 8q23-qter duplication. This report supports that critical gene(s) for cardiac septum formation reside on distal chromosome 8q.